Sonographic diagnosis of perforation of the gastric antrum caused by a foreign body: A case report. Issue 8 (February 2019) - Zhao, Yanan; Yang, Zheng; Quan, Juan; Hu, Huisen
Abstract: Rationale: Ingestion of foreign bodies often occurs in clinical environments, especially in toddlers and aged patients. Although plain radiography and CT are widely used for the assessment of foreign bodies, sonography has an advantage in the diagnosis of some radiolucent foreign bodies, such as wood and bamboo materials. Patient concerns: An 80-year-old woman presented with a 4-day history of right upper quadrant abdominal persistent distended pain without radiation. Diagnoses: Radiographs, a preliminary abdominal ultrasound (US) and an abdominal computed tomography (CT) were unremarkable. A repeat abdominal US found a foreign body inserted in the gastric wall of antrum. But subsequent gastroscopy was negative. A laparotomy confirmed the diagnosis of bamboo stem penetration out of the gastric antrum. Interventions: The patient was treated by laparotomy and the bamboo stem was removed successfully. Outcomes: Bamboo stem-caused digestive perforation was confirmed by laparotomy. The perforation site was at the gastric wall of antrum. Intravenous antibiotic therapy was administered for two weeks until her body temperature dropped to a normal level, and C-reactive protein (CRP) decreased to the normal limits. she was discharged from the hospital. Lessons: Previous studies suggest that US can identify the location and shape of foreign bodies in the alimentary tract in toddlers. This case shows US is also effective in aged patients. The US can be utilized as a problem-solving tool when radiolucent foreign bodies are suspected, especially when the results of CT and gastroscopy are negative.